2019
DOI: 10.1002/andp.201900350
|View full text |Cite
|
Sign up to set email alerts
|

Spin Dynamics and Dirac Nodes in a Kagome Lattice

Abstract: Herein, the spin dynamics for various magnetic configurations arranged on a Kagome lattice is investigated. Using a Holstein–Primakoff expansion of the isotropic Heisenberg Hamiltonian with multiple exchange parameters, the development and evolution of magnetic Dirac nodes with both anisotropy and magnetic field are examined. From the classical energies, the phase diagrams for the ferromagnetic (FM), antiferrimagnetic (AfM), and the 120°  phases are shown as functions of J1, J2, J3, and anisotropy. Furthermore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…The Dirac points are protected here by effective time reversal and inversion symmetries and are therefore gapped out by arbitrarily weak symmetry-breaking perturbations. It is possible to devise realistic models for several different lattices and magnetic structures where Dirac points appear in magnon spectra − in other words where the protecting symmetries are present at least at the linear spin wave level (52,53,54,55,56). This includes the generalization of Dirac crossings to three dimensions where they are four-fold degenerate (57).…”
Section: Dirac Points Nodal Lines and Weyl Pointsmentioning
confidence: 99%
“…The Dirac points are protected here by effective time reversal and inversion symmetries and are therefore gapped out by arbitrarily weak symmetry-breaking perturbations. It is possible to devise realistic models for several different lattices and magnetic structures where Dirac points appear in magnon spectra − in other words where the protecting symmetries are present at least at the linear spin wave level (52,53,54,55,56). This includes the generalization of Dirac crossings to three dimensions where they are four-fold degenerate (57).…”
Section: Dirac Points Nodal Lines and Weyl Pointsmentioning
confidence: 99%
“…This approach is illustrated by applying it to multiple systems ranging from a generalized www.advancedsciencenews.com www.ann-phys.org harmonic oscillator to a spin-half particle in a magnetic field, which is the proto-typical example of a fermionic system. D. Boyko et al, in their original article, [5] examines the spin dynamics of Dirac bosons in the Kagome lattice. Using a spin-spin exchange Hamiltonian, they determine the conditions needed for various spin configurations with multiple nearest-neighbor interactions to modify Dirac nodes.…”
Section: Doi: 101002/andp202000037mentioning
confidence: 99%
“…These types of cluster modes are not unheard of as they have been observed in structures like the pyrochlore lattice [16]. Furthermore, Boyko et al also revealed that, to first order, the 120 • phase mimics the antiferromagnetic (AFM) honeycomb lattice due to the net in and out spin configurations [40]. However, unlike the AFM honeycomb lattice, the Kagome lattice can break this degeneracy with second-and third-order interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, Boyko et al examined the spin-wave dynamics of the Kagome lattice for three different magnetic configurations [out-of-plane ferromagnetic (FM), out-of-plane antiferrimagnetic (AfM), and 120 • phase] and various isotropic nearest, next-nearest, and nextnext-nearest neighbor interactions [40]. In this work, it was shown that, to first order, the FM phase produced three modes, wherein two modes were dispersive, longrange order modes, and one was a non-dispersive, clusterlike flat band.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation